The characteristics of auditorial event-related potential under propofol sedation associated with preoperative cognitive performance in glioma patients - Wang, Xinxin; Yang, Wanning; Jian, Minyu; Liang, Yi; Yang, Zuocheng; Chen, Yiwei; Ma, Bo; Wang, Chengwei; Hou, Zonggang; Deng, Zhenghai; Liu, Haiyang; Xie, Jian; et al. (Frontiers in Neuroscience, 2024)
BackgroundGlioma patients often experience neurocognitive deficits, particularly mild cognitive impairment (MCI), which affects their perioperative safety. The use of auditory event-related potentials (AERPs) might be a promising method for reflecting perioperative cognitive function in patients, even under unresponsive sedation. In this study, we aimed to investigate the relationships between the AERP under sedation and preoperative cognitive performance in glioma patients.MethodsPatients with primary supratentorial gliomas who were scheduled for elective craniotomy under general anesthesia were included in this prospective observational study. The patients were categorized into MCI and non-MCI groups based on their preoperative Montreal Cognitive Assessment (MoCA) scores. AERP characteristics, including mismatch negativity (MMN), P300, and event-related spectral perturbation (ERSP) in the theta bands, were analyzed under different propofol-induced sedation conditions. Differences in these parameters between groups and their relationships with preoperative cognitive performance were subsequently investigated.ResultsTwenty-nine eligible patients were included in the analysis. Compared to that in the non-MCI group, the average amplitude of the MMN component evoked by the novel stimulus significantly decreased during the recovery period in the MCI group (−3.895 ± 1.961 μV vs. -1.617 ± 1.831 μV, p = 0.003). Theta-ERSPs also differed between the two groups under standard (0.021 ± 0.658 μV2/Hz vs. 0.515 ± 0.622 μV2/Hz, p = 0.048) and novel (0.212 ± 0.584 μV2/Hz vs. 0.823 ± 0.931 μV2/Hz, p = 0.041) stimulation conditions under light sedation. After correcting for age, education level, site of lesion, WHO pathological grade and combined symptomatic epilepsy as confounders, the frontal theta-ERSP induced by standard and novel stimuli under light sedation was inversely related to the preoperative MoCA score (standard stimuli: β = −0.491, p = 0.011; novel stimuli: β = −0.594, p = 0.007), as was the average MMN amplitude induced by novel stimuli during the recovery period (β = −0.356, p = 0.035).ConclusionThe AERP neural response characteristics of glioma patients during propofol sedation were associated with preoperative cognitive performance, which might be a potential neurophysiological indicator for monitoring perioperative cognitive function, especially theta-ERSP.